1979
DOI: 10.1002/cjce.5450570205
|View full text |Cite
|
Sign up to set email alerts
|

Flooding and axial dispersion in reciprocating plate extraction columns

Abstract: The flooding and axial mixing characteristics of a 15 cm diameter reciprocating plate extraction column with six different plate arrangements handling kerosene dispersed in water are reported. A general correlation for flooding in the emulsion flow regime is developed and applied to the present results and to published data on other columns and systems. Under certain conditions of flow and agitation, the axial mixing is very high because of circulation, but it can be reduced by including baffles in the plate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 15 publications
6
36
1
Order By: Relevance
“…This trend which was also noted by Hafez et al (1979) and by Karr et al (1987) is due to the observed tendency of the water flow to distribute poorly across the column (fingering). Distribution is improved by moderate agitation; at the highest agitation levels, E is approximately proportional to uh and the relationship is represented approximately by Equation…”
Section: Single Phase (Liquid) Flowmentioning
confidence: 60%
“…This trend which was also noted by Hafez et al (1979) and by Karr et al (1987) is due to the observed tendency of the water flow to distribute poorly across the column (fingering). Distribution is improved by moderate agitation; at the highest agitation levels, E is approximately proportional to uh and the relationship is represented approximately by Equation…”
Section: Single Phase (Liquid) Flowmentioning
confidence: 60%
“…G. Gomaa and A. M. Al Taweel dispersion in a pulsed column equipped with plates similar to those used in a KRPC, in which the axial dispersion coefficient was found to increase with a 2 f , and that of Kim and Baird (1976) in a 0.05 m diameter KRPC, where a similar relation was noted in which E increased with a 1:8 f . The work of Hafez et al (1979) and Baird and Rama Rao (1988) for axial mixing in a 0.15 m and 0.05 m diameter KRPC, respectively, showed a somewhat different trend in which axial dispersion varied linearly with af . Other investigations using different types of columns also showed an increase in dispersion coefficient with the oscillation frequency and amplitude but with different powers (Parthasarathy et al, 1984;Rama Rao et al, 1986).…”
mentioning
confidence: 87%
“…It optimizes two parameters, the MRT and Pe. This model calculates the RTD response of a system to an arbitrary pulse of tracer by convoluting the input function with impulse response of the model [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. It uses the least square curve fitting method to fit the model RTD function (Eq.…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%
“…Effect of various geometrical and operating parameters on the axial mixing of continuous phase has been reported in these investigations [5][6][7][8][9]. Most of these studies have been carried out using visual method after injecting a dye tracer or a conventional method by injecting a non-radioactive tracer and measurements were made by a conductivity probe.…”
Section: Introductionmentioning
confidence: 99%